PENINGKATAN HASIL BELAJAR SISWA TENTANG PERPINDAHAN KALOR MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING DI KELAS V SDK DON BOSKO 1 KOTA KUPANG - Taty R Koroh; Treesly Y. N Adoe; Ovide E. Taek (Journal of Character and ELementary Education, 2023)
This classroom action research study aims to improve student learning outcomes about heat transfer through the discovery learning model. This research is carried out in two cycles with steps, namely: planning, implementation, observation, and reflection. The subjects in this study were 23 students, consisting of 16 girls and 7 boys. Observation, learning outcomes tests, and documentation are the data collection techniques used. The data analysis techniques used are qualitative and quantitative descriptive analysis. The results showed that there was an increase in learning outcomes in each cycle, namely (1) the results of observations of the activities of the first cycle teachers were categorized well with a percentage of 73.12%, the second cycle was categorized as very good with a percentage of 89.76%. (2) the results of observations of the activities of the cycle I students were categorized as good with a percentage of 69.83%, and cycle II was very good with a percentage of 92.24%.(3) the learning outcomes of the cycle I average student score is 66.08 with a completion percentage of 43%, cycle II average score of 89.56 with a completeness percentage of 87%. Therefore, it can be concluded that the discovery learning model can improve student learning outcomes.